2013
DOI: 10.1603/ec11189
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Resistance to Adult Spittlebugs (Hemiptera: Cercopidae) in <I>Brachiaria</I> spp.

Abstract: Nymphs and adults of several spittlebug (Hemiptera: Cercopidae) species are key pests of forage brachiariagrasses (Brachiaria spp.) in tropical America. To support current breeding programs, a series of experiments aimed at characterizing the mechanisms of resistance to adult feeding damage were carried out. Five genotypes were used: two susceptible checks (CIAT 0606 and CIAT 0654) and three nymph-resistant genotypes (CIAT 36087, CIAT 6294, and SX01NO/0102). Test insects were Aeneolamia varia (F.), A. reducta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Because survival of spittlebug nymphs was related to the forages' resistance level, there was also evidence that genotypes RUZ 2, DIG 1 and DIG 2 may be resistant to M. spectabilis via antibiosis. Some literature has already indicated that the species B. ruziziensis is susceptible to spittlebugs . However, this study showed that genotype RUZ 2 had the lowest survival rate and evidenced a genetic variability of the species concerned .…”
Section: Discussionmentioning
confidence: 92%
“…Because survival of spittlebug nymphs was related to the forages' resistance level, there was also evidence that genotypes RUZ 2, DIG 1 and DIG 2 may be resistant to M. spectabilis via antibiosis. Some literature has already indicated that the species B. ruziziensis is susceptible to spittlebugs . However, this study showed that genotype RUZ 2 had the lowest survival rate and evidenced a genetic variability of the species concerned .…”
Section: Discussionmentioning
confidence: 92%
“…In addition to using rangelands and native or naturalized pastures for grazing, farmers seed pastures with improved grasses and legumes and cultivate forage crops for e.g., hay, silage and fresh feed. More recently, i.e., during the last 4-5 decades, plant breeders have made important contributions to livestock productivity by developing high yielding forage varieties with tolerances to biotic and abiotic stresses (e.g., Miles et al, 2006;Miles and Hare, 2007;Aguirre et al, 2013;Cardoso et al, 2013;Rao et al, 2016;Hernandez et al, 2017;Abd El-Naby et al, 2019). Raising yields of forage crops can increase the availability and affordability of livestock products as well as reduce pressure on increasingly scarce land resources by enabling greater herd densities on existing pasture.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of exotic pasture monocultures in Brazil has resulted, over time, in an important increase in the abundance of several species in this order 23 , 24 , especially those with a phytophagous habit. A consequence of this increase has been a greater incidence of pests in Brazilian pastures that cause important losses in the production of both dairy and beef livestock 25 , and are also an important cause of the acceleration of pasture degradation 26 .…”
Section: Introductionmentioning
confidence: 99%